EFEKTIVITAS VIDEO PEMBELAJARAN BERBASIS ETNOMATEMATIKA DALAM MENINGKATKAN KEMAMPUAN MENENTUKAN KELILING BANGUN DATAR PADA ANAK TUNADAKSA - Davi, Najwa Rahmi; Nurhastuti, Nurhastuti; Iswari, Mega; Zulmiyetri, Zulmiyetri (TARBAWI:Journal on Islamic Education, 2024)
The aim of this research is to determine the effectiveness of ethnomathematics-based learning videos to improve the ability to determine the circumference of flat shapes in children with physical impairments. The approach used in this research is SSR with an A-B-A design. This research was carried out in 14 meetings divided into 3 phases, the first phase, namely baseline (A1), was carried out in 3 meetings, showing stable results with a score of 20%. The second phase, namely intervention (B), was carried out in 8 meetings, showed an increase with a score of 70% to 90% and showed stability at the 6th to 8th meetings. The final phase, namely baseline (A2), was carried out in 3 meetings, showing stable results with a score of 90%. These results show an increase in the ability to determine the circumference of flat shapes with ethnomathematics-based learning videos for children with physical impairments.